2017
DOI: 10.1007/s00404-017-4292-1
|View full text |Cite
|
Sign up to set email alerts
|

High-grade serous ovarian cancer: the clone wars

Abstract: BackgroundThe last 5 years’ studies using next-generation sequencing provided evidences that many types of solid tumors present spatial and temporal genetic heterogeneity and are composed of multiple populations of genetically distinct subclones that evolve over time following a pattern of branched evolution. The evolutionary nature of cancer has been proposed as the major contributor to drug resistance and treatment failure. In this review, we present the current state of knowledge about the clonal evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 65 publications
4
43
0
Order By: Relevance
“…It seems initially counterintuitive that the proliferative subtype displayed a lower risk than the mesenchymal subtype with respect to overall survival [8]. However, this is in agreement with several previous studies that found an extreme level of genomic instability associated with improved outcome compared to intermediate levels [26,27]. A recent analysis of transcriptome subtypes in colorectal cancer generally questioned the existence of discrete subtypes, and proposed a continuum of transcriptomes instead [28].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It seems initially counterintuitive that the proliferative subtype displayed a lower risk than the mesenchymal subtype with respect to overall survival [8]. However, this is in agreement with several previous studies that found an extreme level of genomic instability associated with improved outcome compared to intermediate levels [26,27]. A recent analysis of transcriptome subtypes in colorectal cancer generally questioned the existence of discrete subtypes, and proposed a continuum of transcriptomes instead [28].…”
Section: Discussionsupporting
confidence: 82%
“…A subtype model based on HGSOC tumor evolution: our observations are consistent with a model that places the differentiated and the proliferative subtype at opposite ends of the timeline of HGSOC tumor developement; with the differentiated subtype being an early subtype, the proliferative a late subtype, and the immunoreactive and the mesenchymal being intermediate subtypes. HGSOC development along this timeline is thereby reportedly characterized by an increasing level of genomic instability and subclonal expansion [25,26]. Several previous findings support this model: (i) mean age at diagnosis was lowest for patients of differentiated subtype, but significantly increased for patients of proliferative subtype [8], and (ii) tumors of differentiated subtype displayed a high level of infiltrating immune cells, indicating an active immune response at an early time point of tumor development, whereas tumors of proliferative subtype displayed a negligible level of infiltrating immune cells, consistent with an adapted tumor successfully evading the immune response at a late point in tumor evolution [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, conversely, higher levels of genomic instability can enable the acquisition of pathogenic variants with a selective disadvantage, by limiting tumour growth or increasing response to chemotherapy. 14…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Notch and FOXM1 signalling pathways are also implicated . The genomic instability present in HGSOC promotes the development of further variants, increases genetic diversity and development of genetically distinct subclones within a tumour . Genomic instability can be associated with treatment resistance and poor prognosis if subclones develop genomic characteristics that benefit tumour survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation